Receptors for IgA on human thymus cells in myasthenia gravis. - Moraru, I (1982)
Specific surface receptors for the Fc region of human immunoglobulin A (Fc alpha R) were identified on the thymus cells of all 15 patients affected by myasthenia gravis. A large variation of the percentage of Fc alpha R bearing thymus cells was recorded (9 . 5-66 . 0%; mean value 27 . 9 +/- 17 . 8) the high values being associated in most cases with the thymus hyperplasia and the low values with a lipomatosis of the organ. Even the lowest percentage of Fc alpha R bearing cells recorded in myasthenia gravis are considerably higher than those found in normal subjects (0 . 4-4 . 1; mean value 1 . 8) demonstrating that the expression of Fc alpha R on the thymus cells is the consequence of the disease. No attempts were made to identify the cell population bearing Fc alpha R but indirect results indicate that the cells belong to E-rosette forming population, and, in some cases, to a null cell population devoid of the ability to form E and EAC rosettes, Fc alpha R can bind various IgA ligands and the binding is confined to a small fraction of IgA (not more than 5%) considered as cytophilic IgA.